2013
DOI: 10.1002/pen.23768
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of silica reinforced polypropylene: Correlation between morphology and properties

Abstract: Polypropylene/fumed hydrophilic silica nanocomposites were prepared via melt mixing method using a single‐screw extruder. Comparative study with and without compatibilizing copolymer agent (maleic anhydride grafted polypropylene: PP‐g‐AM) was conducted. The obtained results were interpreted in terms of silica nanoparticle–silica nanoparticle and silica nanoparticle‐polymer interactions. These results have shown that the addition of nanofillers improves the properties of the nanocomposites. From transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…For example, high screw speed can give rise to the development of nanostructured blends with properties impossible to reach with classical processing techniques (twin-screw extruder, internal mixer, etc.). Concerning high shear extrusion, Louizi et al [24,25] and Bouaziz et al [26] have recently shown that the final morphology of polymer blends is significantly influenced by extrusion parameters such as mean residence time and screw rotation speed. Moreover, the specific mechanical energy "SME", which characterizes the extrusion process (with parameters such as torque, temperature, rotation speed, and throughput), can be correlated with the quality of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…For example, high screw speed can give rise to the development of nanostructured blends with properties impossible to reach with classical processing techniques (twin-screw extruder, internal mixer, etc.). Concerning high shear extrusion, Louizi et al [24,25] and Bouaziz et al [26] have recently shown that the final morphology of polymer blends is significantly influenced by extrusion parameters such as mean residence time and screw rotation speed. Moreover, the specific mechanical energy "SME", which characterizes the extrusion process (with parameters such as torque, temperature, rotation speed, and throughput), can be correlated with the quality of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐first century materials will be made and tailored to target specification by combining disparate multiple materials to achieve new functionality. Maleic anhydride (MAH) grafting is approved as an effective additive to improve dispersion of silica in non‐polar matrix . Among the grafting techniques, free‐radical melt grafting during extrusion has been considered as one of the most practical and cost‐effective methods.…”
Section: Introductionmentioning
confidence: 99%
“…10 On the contrary, steady increase of Young's modulus with increased silica content indicates preferable reinforcing effect of stiffer silica particles. Additional enchancement of tensile and impact strength was achieved by addition of maleated polypropylene (PP-g-MAH) as a compatibilizer for binary iPP/SiO 2 composites presented in papers by Bikiaris et al and Bouaziz et al 12,13 The hydroxyl groups on the surface of silica nanoparticles react with maleic anhydride groups of PP-g-MAH leading to higher adhesion between iPP matrix and silica particles and finer dispersion of individual SiO 2 nanoparticles with reduced agglomeration. Additional enchancement of tensile and impact strength was achieved by addition of maleated polypropylene (PP-g-MAH) as a compatibilizer for binary iPP/SiO 2 composites presented in papers by Bikiaris et al and Bouaziz et al 12,13 The hydroxyl groups on the surface of silica nanoparticles react with maleic anhydride groups of PP-g-MAH leading to higher adhesion between iPP matrix and silica particles and finer dispersion of individual SiO 2 nanoparticles with reduced agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] However, in order to improve the interfacial stress transfer and to balance the toughness and stiffness in polymer composites an appropriate compatibilizer and/or a rubber toughening agent should be added. 12,13 While the compatibilization of binary and ternary iPP composites was widely explored, [12][13][14][15][16][17][18][19][20][21][22] there are few papers dealing with V C 2014 Wiley Periodicals, Inc. 12,13 While the compatibilization of binary and ternary iPP composites was widely explored, [12][13][14][15][16][17][18][19][20][21][22] there are few papers dealing with V C 2014 Wiley Periodicals, Inc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation